Efektivitas Pemberian Pupuk Organik, Anorganik, dan Hayati terhadap Produktivitas Tanaman Padi (Oryza sativa L.) - Lestari, Citra Ayu; Setiawan, Andri; Putri, Ade Maulydiah; Muqoddam; Khairunnisa, Fahira Dewi; Rahmadi, Rizky; Rochman, Fajar (Politeknik Negeri Lampung, 2024)
The lack of nutrient availability can lead to a decline in rice plant (Oryza sativa L.) productivity. One effort to increase plant productivity is fertilization. The aim of this journal review is to analyze the effectiveness of inorganic, organic, and biofertilizers on rice productivity. The method used is a literature review by analyzing published journals (2010-2024) on the effectiveness of inorganic, organic, and biofertilizers in rice plants. The review results show that inorganic fertilizers provide nutrients quickly; however, their long-term use is detrimental to environmental conditions and sustainable agriculture. Organic fertilizers can enhance soil microorganisms and improve soil structure, although their nutrient content is low. Meanwhile, biofertilizers enhance nutrient availability through nitrogen-fixing microorganisms. The combination of inorganic, organic, and biofertilizers is proven to be more effective in increasing rice productivity without harming the environment. Keywords: Inorganic, Biofertilizer, Organic, Rice, Fertilizer